Implementasi Kebijakan Sistem Informasi Manajemen Berbasis Aplikasi Silasidakep di Kecamatan Sumedang Utara - Fepi Febianti; Desy Farida Valeria; Intan Annisa; Ode Sopian; Ramdan; Tendiyana Nugraha (JRPA - Journal of Regional Public Administration, 2022)
This study aims to find out how the implementation of the management information system policy for the Silidakep application and the constraints of the implementation of the information system in North Sumedang District are able to optimize the work of employees serving the community in the field of population and civil registration. Data was collected through library and field studies including: observation, interviews, documentation studies and triangulation. Determination of the sample/informant in this study was carried out using purposive sampling. Furthermore, data analysis was carried out by referring to the technical analysis of the Miles and Huberman model, namely: data reduction (data reduction), data display (data presentation), and conclusion drawing/verification (conclusions). The implementation of the policy on the use of the siladakep application at the North Sumedang District Office has been running but is still not good. This happened because of obstacles such as: (1) Lack of understanding of the siladakep application because the community had not received comprehensive socialization, (2) the community had not received comprehensive socialization, one of which was caused by most of the employees not mastering the siladakep application, (3) The lack of stability of the internet network due to the use of this siladakep application, the main element is the internet network as a supporter of access to the entry of the application. With the end of writing this report, our researchers suggest that the leadership of the North Sumedang District Office should further improve the facilities in the office, and give more attention to employees so that they are more aware of carrying out and completing their duties optimally